Precuneus activation correlates with the vividness of dynamic and static imagery: an fMRI study - Suna Duan; Suna Duan; Qingfeng Li; Junjie Yang; Qing Yang; Enran Li; Yuting Liu; Lijuan Jiang; Chunbo Li; Binglei Zhao; Binglei Zhao (Frontiers in Human Neuroscience)
IntroductionVisual mental imagery (VMI) is a cognitive function that significantly impacts various aspects of daily life. However, the neural correlates of VMI vividness remain unclear, especially underlying different VMI types. Therefore, the current functional magnetic resonance imaging (fMRI) study aimed to investigate the neural mechanisms underlying static (SI) and dynamic VMI (DI), focusing on the role of precuneus especially in the imagery vividness.MethodsThe study involved 24 participants recruited from ShanghaiTech University. After excluding four participants due to excessive movements, data from 20 participants were analyzed. Each participant completed the Chinese version of the Vividness of Visual Imagery Questionnaire (VVIQ) to assess their imagery vividness abilities. During fMRI scanning, participants were asked to imagine SI and DI scenarios in response to auditory stimuli. High-resolution fMRI data were acquired using a 3T scanner, and a General Linear Model (GLM) was applied to analyze blood oxygenation level-dependent (BOLD) signals, focusing on the precuneus’s role in imagery vividness.ResultsThe results revealed that the left precuneus was found activated in both SI and DI tasks. Moreover, the left precuneus activation was positively correlated with VVIQ score. On the other hand, greater activation in the right precuneus was found during dynamic than static imagery as well as more extensive neural engagements; the right precuneus activation was further detected significantly correlated with individual VVIQ scores.DiscussionThe study’s findings offered fresh insights into the cognitive and neural processes subserving VMI. By revealing the distinct roles of the left and right precuneus in imagery vividness, this research contributed to a more nuanced understanding of VMI and its neural basis.